Análise de gerações e estratégias de seleção em genótipos de soja visando resistência à ferrugem asiática e produção de grãos - Bernardes, Fernanda da Silva (2019)
Asian rust causes significant damage to soybean crops, thus, the use of cultivars that grow faster and are resistant has been the target of breeding programs to alleviate losses in grain yield. The cultivar development process follows several steps, and to choose the best method, the use of genetic parameter estimates, such as those obtained in the analysis of generations, allows better study and definition of breeding strategies. In addition, selecting superior genotypes requires a simultaneous evaluation of all target characters in the breeding, so the selection index becomes an alternative. This dissertation was divided into three chapters, the first chapter being a bibliographical review on the importance of culture, the genetic improvement of soybean and Asian rust. The second chapter aimed to evaluate genetic parameters and to estimate selection gains in two combinations involving parents with resistance to Asian rust. This study was carried out at the Capim Branco experimental farm of the Federal University of Uberlândia. Agronomic characters and rust severity were evaluated for the two F2 combinations from the hybridizations between UFUS 6901 x TMG 801, UFUS 6901 x BRSGO 7560 and their respective backcrosses. The two combinations allowed to estimate genetic parameters and indicated variability for the segregating populations F2, RC1 and RC2.The combination of UFUS 6901 and TMG 801 allowed the selection of superior individuals regarding grain production and the combination UFUS 6901 and BRSGO 7560 for rust severity. In chapter three, a research was carried out aiming at determining genetic parameters, estimating phenotypic and genotypic correlations in F3 progenies from two populations with parents resistant to Asian rust; to select F3 progenies from two populations with high productivity and less resistance to rust. The experiment was carried out in the field of the UFU Soybean Improvement Program, in the municipality of Uberlândia - MG, in the 2018/2019 harvest. We evaluated 87 soybean genotypes of the combination UFUS 6901 x TMG 801 and 87 soybean genotypes of the combination between UFUS 6901 x BRSGO 7560. The controls used were: UFUS 6901, TMG 801 and BRSGO 7560. The design was the complete randomized blocks with three replicates. It was verified the existence of genetic variability in both populations. The population UFUS 6901 x TMG 801 presented progenies with high grain yields whose estimates ranged from 3935,46 to 4734,58 kg ha- 1. It was also verified the existence of genetic and phenotypic correlation above 0,9 and positive sign between the characters severity of rust and disease progression. The selection gains regarding grain yield ranged from 1,69% to 14,91% for the strategies respectively. It was possible to select progenies UFUS FB 12 from UFUS 6901 x TMG 801; and progenies UFUS FB 37 from the population UFUS 6901 X A BRSGO 7560.